The premature decay of rifting processes in the northern South China Sea (38–33.9 Ma): insight from 3D seismic and its interpretation of the Lufeng Sag of the Pearl River Mouth Basin. Issue 2 (17th February 2022) - Ma, B. S.; Ge, J. W.; Wu, G. H.; Qi, J. F.; Yu, F.; Chen, S.; He, W. G.
Abstract: A marked transition in depositional signatures within the second rift phase (RP2, 38–33.9 Ma) in the Lufeng Sag, a proximal domain on the northern continental margin of the South China Sea (SCS) has been previously documented. This study integrates seismic data, fault paleo-throw, strain and depth-to-detachment to demonstrate the structural variability in time and space during the early to late stage of RP2 in the Lufeng Sag and investigates the rifting transition and its relationship with rifting processes on the northern SCS margin. The results indicate that extensional deformation transferred from south to north within the Lufeng Sag during RP2 and the rifting in the South Sub-sag was weaker than in the North Sub-sag during both the early and late stages. This structural variability may be related to the basement uplift in the southeast caused by the remote effect of plate movement and magmatic underplating under the Dongsha Uplift. A change of basin geometry from wedge-shaped to nearly tabular, strongly reduced paleo-throws and strains, and sharply increased depth-to-detachment from the early to late stage indicates the premature decay of rifting before the breakup of the SCS. This transition may be influenced by the opening of the Northeast Sub-basin of the SCS at ca 37 Ma, where extensional strain sharply concentrated, and led to the waned rifting of the Lufeng Sag. The study thus provides new insights into rifting processes along the northern SCS margin that can be applied to similar basins elsewhere. KEY POINTS: Basin geometry, fault paleo-throw, strain and depth-to-detachment analysis demonstrate a weakened rifting in the Lufeng Sag (38–33.9 Ma). Structural variability between the South and North sub-sags may be caused by the remote effect of plate movement and magmatic underplating during the Dongsha Uplift. Structural transitions in the Lufeng Sag indicate a premature decay of rifting before the breakup of the SCS, which was caused by thermal subsidence and regional plate subduction.